Examining the effect of intermittent cycling throughout a 3-h period on peripheral blood concentrations of haemopoietic stem and progenitor cells and cytolytic natural killer cells - Phoebe A. Cox; Fendi Pradana; Ella Noble; Samuel J. E. Lucas; Guy Pratt; Mark T. Drayson; Kevin Amin; Francesca A. M. Kinsella; Alex J. Wadley (Stem Cell Research & Therapy)
Abstract Background Peripheral blood stem cell (PBSC) donation is the primary procedure used to collect haemopoietic stem and progenitor cells (HSPCs) for haemopoietic stem cell transplants (HSCT), however there is a clinical need to reduce collection times and achieve sufficient HSPC doses for successful engraftment. Short bouts of interval cycling transiently enrich peripheral blood with HSPCs and cytolytic natural killer (CD56dim NK) cells, which predict engraftment success and prevent post-transplant complications respectively. Despite this, feasible protocols for use during PBSC collections (≈ 3 h) have yet to be evaluated. Methods In a randomised crossover design, 18 adults (9 young: 22.7 ± 3.2 years, 9 older: 65.2 ± 12.9 years) completed 3 × 3-h trials: high-intensity interval exercise (HIIE, 9 × 2-min cycling at 80–85% heart rate (HR)max/9 × 18 min rest), moderate-intensity interval exercise (MIIE, 9 × 4-min cycling at 65–70% HRmax/9 × 16 min rest) and REST (180 min). Immune cell subsets, including HSPCs and CD56dim NK concentrations (cells/µL) were determined across 18 timepoints and area under the curve (AUC, cells/µL x minutes) and total cell dose (cells/kg) were estimated. Results By design, MIIE elicited lower average and peak HR and rating of perceived exertion than HIIE and was reported as more enjoyable. All cell subset concentrations increased following each interval of MIIE and HIIE. Across all participants, the estimated cell dose of total lymphocytes, monocytes, T cells, CD56bright and CD56dim NK was greater in MIIE and HIIE versus REST (p < 0.03), but there were no differences between MIIE and HIIE. The magnitude of change versus REST was greatest for CD56dim NK versus all cell subsets, and AUC was significantly greater in HIIE versus REST for this cell type only (p < 0.0001). There were no statistically significant differences in HSPC AUC (p = 0.77) or cell dose (p = 0.0732) in MIIE and HIIE versus REST. Age did not predict any changes across trials or timepoints for any cell type. Conclusion Persistent mobilisation of peripheral blood immune cells throughout 3 h of MIIE and HIIE evoked sustained numbers of CD56dim NK cells, but there was no reliable difference in HSPCs compared to a time-matched period of rest.